A Proposal for the Validation of Categories on Strategic Cost Management - Wrubel, Franciele; Diehl, Carlos Alberto; Toigo, Leandro Augusto; Ott, Ernani (Review of Business Management, 2011)
The Strategic Cost Management (SCM) is a matter of wide discussion among researchers because it is an overarching theme, which reaches all organizations, with significant impacts on the strategy. SCM has developed and expanded, without having reached a consensus on the practices referred to it. The main objective of this paper was to propose a set of categories on the SCM. To this end, we have carried out literature search to map terms related to SCM and thereby develop a set of categories and subcategories. It is perceived that there was no agreement among different authors on the practices that can be considered within the scope of this area. The initial categories were defined based on the key topics proposed by Shank and Govindarajan (1997): cost drivers analysis, value chain analysis and strategic positioning analysis. To validate them it was used the Delphi technique round, when 17 categories and 124 subcategories were sent to three experts in the field, recognized for their expertise in research, academic and distinguished role in forums related to this approach. Through three rounds we have obtained a consensus and validated to 16 categories and 84 subcategories. The theme is the most extensive Value Chain Analysis, with 48 practices, followed by Cost Drivers Analysis (22) and finally by the Strategic Positioning Analysis (14). Thus, it was revealed an extensive set of practices that could be validated by establishing a set of categories related to SCM, which may serve as a basis for future research in this area. Key words: Categories. Strategic cost management. Framework.